Economic transformation in Africa from the bottom up: Evidence from Tanzania - Diao, Xinshen; Kweka, Josaphat; McMillan, Margaret S. (International Food Policy Research Institute, 2017)
At roughly 4% per annum, labor productivity in Tanzania has grown more rapidly over the past 14 years than at any other time in recent history. Employment growth has also been strong keeping up with population growth at roughly 2.2 percent per annum. However, the bulk of the employment growth – 88.6% - has been in the non-agricultural and largely informal private sector. Using Tanzania’s first nationally representative survey of micro, small and medium sized enterprises - we show that firms in the informal sector contributed roughly half a percentage point to economywide labor productivity growth in Tanzania between 2002 and 2012. However, virtually all of the labor productivity growth contributed by informal firms came from a small subset of firms we call the inbetween firms. We consider attributes of the inbetween firms that could be used for targeting financial and business services to firms with the potential to grow. We find two salient characteristics of firms in the inbetween sector that might lend themselves to targeting – their owners are more likely to keep written accounts and they are more likely to keep their savings in formal bank accounts.